The Influence of Internal Locus of Control And Work Overload On Employee Performance Through Work-Life Balance In The Teleworking Era (Study On Consultant Sector Freelancers in Indonesia) - Maulidya Alfi Anita Zain; Danardana Murwani; Madziatul Churiyah (Citakonsultindo, 2023)
The purpose of this study is to analyze the effect of internal locus of control and work overload on employee performance through work-life balance in the teleworking era for freelancers in the consulting sector in Indonesia. This research is explanatory quantitative research using SEM-PLS as an analytical tool. Questionnaires were distributed via g-form with a total of 154 respondents. Internal locus of control has no significant effect on work-life balance. Work overload has a significant effect on work-life balance. internal locus of control has a significant effect on employee performance. Work overload has no significant effect on employee performance. Work-life balance has no significant effect on employee performance. There is no significant effect between internal locus of control on employee performance through work-life balance. There is no significant effect between work overload on employee performance through work-life balance. The theoretical implication of this research is that freelancers in the consulting sector in Indonesia can improve their internal locus of control to improve performance and be able to manage work, so they don't experience work overload. In addition, this research is expected to be able to contribute to future studies related to internal locus of control, work overload, work-life balance, and employee performance